Sinergi Pengelolaan Wilayah Desa Wisata Serang, Kabupaten Blitar, Jawa Timur - Sundari, Sundari; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
Serang Village is one of the tourism village located in Blitar and initiated in 2014. The area of Serang Tourism Village is generally located on land owned by the local communities and Perum Perhutani. But in its management, the Department of Youth, Sport, Culture, and Tourism of Blitar Regency especially tourism sector also become a part of management tourism in Serang Village. It required a synergy between the parts related to the management of the area in Serang Tourism Village. This study aims to determine synergy in the management of the area in Serang Tourism Village. This research is located in Serang Tourism Village, Panggungrejo Subdistrict, Blitar Regency. The data used in this study is qualitative data with the data source in the form of primary data and secondary data. The data were collected using the method of observation, in-depth interview, and literature study. The determination of informants used purposive method. The results show that the total area of Serang Tourism Village is ??928.858 Ha and territorially divided into three (3) territories namely Serang I, Serang II, Serang III. In tourism activities, especially in the area of ??Serang Beach in Serang Tourism Village is located on government land and in this case managed by Perum Perhutani. Synergy in the management of Serang Tourism Village area identified based on several stages, including planning, organizing, directing, and controlling.   Keywords : Tourism Vilage, Synergy, Management, Mapping Of Territories